PENERAPAN SISTEM INFORMASI PELAYANAN PERIZINAN TERPADU (SIPINTER) DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN TANGERANG - Nur Annisaa; Riny Handayani (Indonesian Journal of Social Science and Education (IJOSSE), 2026)
Abstract This study aims to analyze the implementation of the Integrated Licensing Service Information System (SIPINTER) at the Investment and One-Stop Integrated Services Office (DPMPTSP) of Tangerang Regency. The research is grounded in issues of low institutional responsiveness in following up on complaints, mismatches between actual service completion time and the Standard Operating Procedure (SOP), and uneven public socialization of the system. This study employs a descriptive method with a qualitative approach, using 3-dimensional e-government success model, namely Support, Capacity, and Value, as the analytical framework. Data were collected through field observation, regulatory documentation review, and in-depth interviews. The findings indicate that the Support dimension is backed by strong political will, allocated funding, and multi-channel socialization that has driven growth in registered users, though technical assistance responsiveness outside office hours remains weak. The Capacity dimension shows adequate human resources and staff competence, but the technological infrastructure remains prone to disruptions such as OTP delivery failures and server downtime. The Value dimension has produced tangible benefits in efficiency and service transparency, yet this value is undermined by document processing delays exceeding SOP standards, driven by a "digital red tape" practice among internal verification officers. This study recommends strengthening online technical support and adopting contingency resource mechanisms to improve service. Keywords: SIPINTER, e-government, licensing service, DPMPTSP, Support-Capacity-Value model Abstrak Penelitian ini bertujuan untuk menganalisis Penerapan Sistem Informasi Pelayanan Perizinan Terpadu (SIPINTER) di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kabupaten Tangerang. Latar belakang penelitian ini didasari oleh masih rendahnya responsivitas instansi dalam menindaklanjuti laporan, ketidaksesuaian durasi penyelesaian layanan dengan Standar Operasional Prosedur (SOP), serta sosialisasi yang belum merata kepada masyarakat. Penelitian menggunakan metode deskriptif dengan pendekatan kualitatif, dengan analisis berlandaskan model keberhasilan e-government tiga dimensi yaitu Support, Capacity, dan Value. Hasil penelitian menunjukkan bahwa dimensi Support telah didukung oleh political will yang kuat, alokasi anggaran, dan sosialisasi multikanal yang mendorong pertumbuhan pengguna terdaftar, namun masih lemah dalam responsivitas bantuan teknis di luar jam kerja. Dimensi Capacity menunjukkan kecukupan sumber daya manusia dan kompetensi petugas, tetapi infrastruktur masih rentan mengalami gangguan teknis seperti kegagalan pengiriman OTP dan server down. Dimensi Value menghasilkan manfaat nyata berupa efisiensi dan transparansi pelayanan, namun nilainya terdegradasi akibat keterlambatan penyelesaian dokumen yang melampaui SOP, yang dipicu oleh praktik birokrasi digital (digital red tape) di tingkat verifikator internal. Penelitian ini merekomendasikan penguatan dukungan teknis daring serta penerapan mekanisme kontingensi sumber daya untuk meningkatkan layanan. Kata Kunci: SIPINTER, e-government, pelayanan perizinan, DPMPTSP, model Support-Capacity-Value